Exploring Fillers in EFL Classroom Interaction: A Case from an Indonesian English Course - Dakoranis, Fatwadika Adinia; Widihastutik, Amelia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Fillers act as a crucial role in cognitive processing and discourse management, particularly in English as a Foreign Language. Most of the previous studies found that they highlighted the fillers in teacher-student interaction in formal education settings. They provide little insight into their role in informal, online EFL classes where interaction is more dynamic and semi-structured. Therefore, this study aims to explore the types of fillers and identify the most dominant fillers in an online English course. It also examines the functions of fillers in an informal classroom. This research used a qualitative approach and classroom discourse analysis (CDA) as the research design, supported by conversation analysis as the framework. The participants of this study are 18 students of the English Conversation Class. The data were gathered through classroom observation and a video recording from an online English course. Three instruments were used in this study: the observation sheet, the coding sheet, and the table analysis. The data were analyzed using the six steps of thematic analysis by Braun and Clarke (2006). Theory triangulation was used to validate the data. This study revealed that the combination of types of fillers, both lexicalized and unlexicalized, and the most common fillers that appeared in the teacher's speech were 88.81% lexicalized, while the students' 84.03% unlexicalized in an informal education setting. It also revealed that three functions of fillers were implemented in the classroom interaction, including cognitive function, social function, and discourse regulatory function.